The Effect of ASEAN Open Skies Policy 2015 Upon Opportunities for Low-Cost Carriers in Indonesia – A Case Study of PT. Citilink - Nurhendiarni, Sri; Hidayat, Nila K.; Pasasa, Linus (The South East Asian Journal of Management, 2015)
The ASEAN Open Skies agreement is included in the ASEAN Economic Community’s blueprint and will be implemented in 2015. This study is intended to assist Citilink - an Indonesian low-cost carrier airline - in measuring its level of awareness and analyzing its SWOT towards the ASEAN Open Skies Policy 2015. This descriptive study utilizes quantitative and qualitative approaches and collected data from both primary and secondary sources. Questionnaires were distributed to Citilink Staff and analyzed using IBM SPSS and SPSS Amos. The awareness level of Citilink staff towards the ASEAN Open Skies Policy turned out to be high and the knowledge factor significantly influenced the awareness level. The study identified both benefits and drawbacks to the implementation of the ASEAN Open Skies Policy; however, Citilink already holds a good position as an Indonesian low-cost carrier and must pursue an aggressive strategy to maximize opportunities so that it can compete successfully at the regional level.